Anterior cervical spine surgery-associated complications in a retrospective case-control study - Tasiou, Anastasia (J Spine Surg, 2017)
Anterior cervical spine procedures have been associated with satisfactory outcomes. However, the occurrence of troublesome complications, although uncommon, needs to be taken into consideration. The purpose of our study was to assess the actual incidence of anterior cervical spine procedure-associated complications and identify any predisposing factors. A total of 114 patients undergoing anterior cervical procedures over a 6-year period were included in our retrospective, case-control study. The diagnosis was cervical radiculopathy, and/or myelopathy due to degenerative disc disease, cervical spondylosis, or traumatic cervical spine injury. All our participants underwent surgical treatment, and complications were recorded. The most commonly performed procedure (79%) was anterior cervical discectomy and fusion (ACDF). Fourteen patients (12.3%) underwent anterior cervical corpectomy and interbody fusion, seven (6.1%) ACDF with plating, two (1.7%) odontoid screw fixation, and one anterior removal of osteophytes for severe Forestier’s disease. Mean follow-up time was 42.5 months (range, 6–78 months). The overall complication rate was 13.2%. Specifically, we encountered adjacent intervertebral disc degeneration in 2.7% of our cases, dysphagia in 1.7%, postoperative soft tissue swelling and hematoma in 1.7%, and dural penetration in 1.7%. Additionally, esophageal perforation was observed in 0.9%, aggravation of preexisting myelopathy in 0.9%, symptomatic recurrent laryngeal nerve palsy in 0.9%, mechanical failure in 0.9%, and superficial wound infection in 0.9%. In the vast majority anterior cervical spine surgery-associated complications are minor, requiring no further intervention. Awareness, early recognition, and appropriate management, are of paramount importance for improving the patients’ overall functional outcome.